OPTIMALISASI PEMBUATAN SABUN DARI MINYAK JELANTAH OLEH PKK DOLOK MARAJA KECAMATAN TAPIAN DOLOK SIMALUNGUN - Rudi Salman; Herlinawati Herlinawati; Irfandi Irfandi; Mukti Hamjah Harahap; Dewi Endriani (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of community partnership activities is to help the partner group of women for Family Empowerment and Welfare (PKK) Nagori Dolok Maraja in utilizing used used oil waste by taking appropriate treatment so that it does not cause disease for the body and does not harm the natural ecosystem. The problem that exists in the community is waste of used cooking oil which is wasted and damages the water ecosystem. The location selection was due to the fact that there are people in the village who are entrepreneurs in the field of home industry and do not yet have economic independence. Besides that, they also have difficulties in developing their business. From the activities carried out, data was obtained during the training and assistance in making liquid soap 9 participants (24%) with very good categories, 10 participants (26%) in good categories, 16 participants (42%) in the Enough category and 3 Participants (8%) were in the poor category. The method used in this activity is assistance and the process of making soap from waste used cooking oil. Assistance and guidance starting from the aspect of awareness about health in consuming cooking oil, the use of waste oil into soap, the production process using appropriate technology so as to give birth to people who are able and economically independent and conservation.